Amniotic fluid cell‐free DNA in preterm prelabor rupture of membranes. (28th October 2018) - Kacerovsky, Marian; Vlkova, Barbora; Musilova, Ivana; Andrys, Ctirad; Pliskova, Lenka; Zemlickova, Helena; Stranik, Jaroslav; Halada, Petr; Jacobsson, Bo; Celec, Peter
Abstract: Introduction: We evaluated the levels of cell‐free nuclear DNA (nDNA) and cell‐free mitochondrial DNA (mtDNA) in the amniotic fluid supernatant from pregnancies complicated by preterm prelabor rupture of membranes (PPROM) based on evidence of microbial invasion of the amniotic cavity (MIAC) and/or intra‐amniotic inflammation (IAI). Material and methods: A total of 155 women with PPROM were included in this study. Amniotic fluid samples were obtained by transabdominal amniocentesis. The levels of cell‐free nDNA and mtDNA in the amniotic fluid supernatant were assessed and quantified by real‐time polymerase chain reaction. Results: The levels of cell‐free nDNA and mtDNA were higher in women with MIAC and IAI than in women without these conditions (nDNA: with MIAC: median 3.9 × 10 4 genome equivalent [GE]/mL vs without MIAC: median 1.2 × 10 4  GE/mL, with IAI: median: 5.3 × 10 4  GE/mL vs without IAI: median 1.2 × 10 4  GE/mL; mtDNA: with MIAC: median 9.2 × 10 5  GE/mL vs without MIAC: median 2.5 × 10 5  GE/mL, with IAI: median 1.1 × 10 6  GE/mL vs without IAI: median 2.5 × 10 5 ; all P values ≤ 0.01). Women with the microbial‐associated IAI showed the highest levels of cell‐free nDNA and mtDNA. Conclusions: Cell‐free nDNA and mtDNA are constituents of the amniotic fluid supernatant from PPROM pregnancies. Both cell‐free nDNA and mtDNA are involved in the intra‐amniotic inflammatory response in women with PPROM. Abstract : What's already known about this topic? Although many studies have evaluated cell‐free DNA in systemic circulation, amniotic fluid cell‐free DNA has not been widely examined. There is a lack of information regarding amniotic fluid cell‐free DNA in pregnancies complicated by preterm prelabor rupture of membranes. What does this study add? This study confirms that cell‐free DNA is a constituent of the amniotic fluid supernatant from pregnancies complicated by preterm prelabor rupture of membranes and is involved in the intra‐amniotic inflammatory response.